Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.yebeh.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather on seizure frequency — Clinical experience in the emergency room of a tertiary hospital

Abstract: Introduction: Some patients with epilepsy identify weather as a typical seizure trigger. However, it is yet to be confirmed. Thus, we aimed to evaluate possible relationships between daily meteorological conditions and the daily incidence of seizures. Methods: This was a retrospective single center study that included adult patients who were admitted to the emergency room of a tertiary hospital in Lisbon, with a seizure, between January and December 2015. The influence of temperature, atmospheric pressure, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…Cyclical but irregular changes in weather, including barometric pressure, external temperature, and air humidity, may play an additional role in modulating the risk of seizures. Seizures are typically thought to occur on “dull gray days” but do not strictly synchronize with weather patterns 8,27–29 . Solar storms, tidal cycles, and other celestial phenomena often have cyclical behaviors, but seizures do not synchronize to external cues at these timescales (Figure 2).…”
Section: Putative Zeitgebersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclical but irregular changes in weather, including barometric pressure, external temperature, and air humidity, may play an additional role in modulating the risk of seizures. Seizures are typically thought to occur on “dull gray days” but do not strictly synchronize with weather patterns 8,27–29 . Solar storms, tidal cycles, and other celestial phenomena often have cyclical behaviors, but seizures do not synchronize to external cues at these timescales (Figure 2).…”
Section: Putative Zeitgebersmentioning
confidence: 99%
“…The existence of endogenous circannual modulation of cortical excitability was also suggested by experiments on mice kept in a constant environment 34–36 ; however, longitudinal assessment in the same animal was lacking. Epidemiological cross‐sectional data, such as admission rates to emergency departments or seizure counts on the neurology ward, suggest that seizure rates tend to increase in winter 29,37,38 (but see 39 ) across patients, with possible contribution from cold weather, 28,29 daylight duration, 37 and seasonal illnesses leading to febrile seizures in children 40 . Some authors have even speculated that light therapy, effective in the treatment of seasonal depression, could be an add‐on approach in epilepsy to “smooth out some of the seasonal peaks in seizure frequencies.” 37,41 …”
Section: Putative Zeitgebersmentioning
confidence: 99%
“…Several studies have shown that meteorological factors such as temperature are associated with hospital admissions for epilepsy attacks (3,(11)(12)(13)(14), therefore we adjusted for average daily temperature and relative humidity. The degree of freedom (df) for the smoothers is determined with Generalized Cross Validation (GCV) and by using the mgcv package in R software.…”
Section: Discussionmentioning
confidence: 99%
“…Precision digital interventions can be adjusted for stressful or traumatic events (personal and family accidents, wildfires) which could trigger additional anxiety and/or depression (Graham et al, 2019). Since atmospheric conditions can impact people with epilepsy (Xu et al, 2016;Brás et al, 2018;Chang et al, 2019), cardiovascular diseases (Stewart et al, 2017), arthritis (Savage et al, 2015), or seasonal affective disorders (Wirz-Justice, 2018), digital therapy can include algorithms which take into account weather forecast. These examples illustrate a unique potential of digital health technologies to optimize interventions based on predictability of seasonal factors and weather forecast.…”
Section: The Immune Systemmentioning
confidence: 99%